2014
DOI: 10.15185/izawol.47
|View full text |Cite
|
Sign up to set email alerts
|

Effect of international activity on firm performance

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…This paper argues that this is largely a consequence of firm under-performance. Evidence shows that better performing firms tend to enter international markets and that internationally active firms are larger, more productive, and pay higher wages than other firms in the same industry that are active only in their home market and vice versa (Wagner, 2014).…”
Section: Low Firm Performance and Weak International Connectionsmentioning
confidence: 99%
See 3 more Smart Citations
“…This paper argues that this is largely a consequence of firm under-performance. Evidence shows that better performing firms tend to enter international markets and that internationally active firms are larger, more productive, and pay higher wages than other firms in the same industry that are active only in their home market and vice versa (Wagner, 2014).…”
Section: Low Firm Performance and Weak International Connectionsmentioning
confidence: 99%
“…This has been highlighted repeatedly both in the media (headlines like "New Zealanders get low wages" -Rosenberg, 2011; and "David Clark: The PM's cleaner deserves more pay" -New Zealand Herald, 2012a) and in academic studies (Healy, 2003;Department of Labour, 2006 57 Better Performing Firms ENGAGE in international activities. Wagner (2014) cited many empirical studies, written since the early 1990s, showing a positive association between firm performance and international market engagement. He suggested that because of the additional costs of participating in the foreign market, higher performing firms tend to self-select into international activities (i.e.…”
Section: Low Firm Performance and Weak International Connectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper argues that this is largely a consequence of firm under-performance. Evidence shows that better performing firms tend to enter international markets and that internationally active firms are larger, more productive, and pay higher wages than other firms in the same industry that are active only in their home market and vice versa (Wagner, 2014).…”
Section: Low Firm Performance and Weak International Connectionsmentioning
confidence: 99%